Alteration of Human Growth Hormones Associated with Moderate Intensity Exercises among Female Students - Alamgir Khan; Umbar Saddique; Muhammad Zafar Iqbal Butt (The Sky, 2024)
The functions of Human Growth Harmons (HGH) include growth, metabolism, and healing, and its level may be influenced by exercise. Growth Hormones link the production of Insulin Growth Factor-1 (IGF-1) development by increasing the glucose level in athletes. This study aimed to examine the impact of moderate intensity on HGH levels among female students. An experimental research design was used in this study, female students were randomly selected, representing a diverse range of body types and baseline health statuses from Punjab University in Lahore. The participants were divided into the experimental group (EG) and the control group (CG). Every group consisted of ten (10) participants. Ethical approval was taken from the ethical review and research board at the University of the Punjab Lahore. Subjects of the experimental group (EG) were given Eight (08) weeks of exercise protocol 5 days per week 40 minutes per day will be applied to the participants of the study, which exercise program included walking, slow running, fast and then slow running Pre and posttest were gathered Human Growth Harmons (HGH) level. Pre and post-tests were managed through the statistical package for social sciences (SPSS-32), and appropriate statistical tests will be applied. Based on data analysis and findings, the researcher concluded that has a positive impact on HGH levels.